Improved Education by Novel Economic Instruments - Stenis, Jan (New Innovations in Economics, Business and Management Vol. 7, 2022)
Objectives: To improve education, the Naturally Optimised Revenue Demand in Communities (NORDIC) model was used. Dropout is a major issue. Dropping out means leaving high school, college or university for practical reasons, necessities, or disillusionment. It has an impact not just on the student who drops out, but also on the university and society as a whole. Based on the NORDIC model, this paper presented a novel and effective economic instrument for enhanced dropout management. Methods: The proposed model generated artificial shadow costs that could be put into government accounts to create economic incentives to reduce dropout rates. The ensuing shadow cost, as well as its impact on the PSBR, form a single essential component that represents the success of the education strategy over time by a single digit. The newly introduced model took into account the age of students who have completed a BSc. This case study demonstrated how the NORDIC model, which is a system of student-government cooperation, may be used to improve education in Swedish society. Results: The findings suggest to a promising methodology for employing economic tools to reduce the dropout rate and lower the qualification age. The NORDIC model has the potential to enhance education systems and qualification ages, notably for BScs. Conclusions: Governments have access to a tool for monitoring, managing, and evaluating the education sector. End users could include school administrators and legislators looking for a complete tool to rethink education policy. To reduce the qualification age, the NORDIC model should be applied to education difficulties. Further study will focus on designing algorithms for certain student groups.